Remission Achieved in Refractory Advanced Takayasu Arteritis Using Rituximab - D. Ernst; M. Greer; M. Stoll; D. Meyer-Olson; R. E. Schmidt; T. Witte (Case Reports in Rheumatology)
A 25-year-old patient was referred due to subclavian stenosis, identified on echocardiography. She presented with exertional dizziness and dyspnoea. Questioning revealed bilateral arm claudication. Examination demonstrated an absent right ulnar pulse and asymmetrical brachial blood pressure. Bruits were evident over both common carotid arteries. Doppler ultrasound and MRI angiograms revealed occlusion or stenosis in multiple large arteries. Takayasu arteritis (TA) was diagnosed and induction therapy commenced: 1 mg/kg oral prednisolone and 500 mg/m2 intravenous cyclophosphamide (CYC). Attempts to reduce prednisolone below 15 mg/d proved impossible due to recurring disease activity. Adjuvant azathioprine 100 mg/d was subsequently added. Several weeks later, the patient was admitted with a left homonymous hemianopia. The culprit lesion in the right carotid artery was surgically managed and the patient discharged on azathioprine 150 mg/d and prednisolone 30 mg/d. Despite this, deteriorating exertional dyspnoea and angina pectoris were reported. Reimaging confirmed new stenosis in the right pulmonary artery. Surgical treatment proved infeasible. Given evidence of refractory disease activity on maximal standard therapy, we initiated rituximab, based on recently reported B-cell activity in TA.